Economic and Legal Policy of the State in the Field of Digital Economy - Vinnyk, Oksana M.; Zadykhaylo, Dmytro V.; Honcharenko, Olena M.; Shapovalova, Olga V.; Patsuriia, Nino B. (International Journal of Criminology and Sociology, 2021)
Digitalisation of the economic sphere of Ukraine is one of the priority areas of social development, which should be reflected in the economic and legal policy of the state. Therewith, a considerable gap exists in the statutory consolidation of the fundamental principles of such a policy, in particular the lack of relevant provisions on the digital transformation of the economy in the Commercial Code of Ukraine. Despite the fact that the state has adopted some acts on the development of the digital economy, there are significant gaps in the legislation, especially with regard to the role of digitalisation in the economic and legal policy of the state. The purpose of the study is a theoretical analysis of the general principles of such a policy in the modern period. As a result, the impact on the economic and legal policy of the state of the process of digitalisation of the economic sphere of the country is determined. The necessity of co-regulation is substantiated, which constitutes a combination of state regulation with self-regulation by participants of digitally-targeted markets. The role of digital resources (on the example of public registers) and electronic financial services is analysed. It is established that the modern legal support of the digital economy needs to be reformed, first of all, by supplementing the Commercial Code of Ukraine with provisions on digitalisation, including the relevant direction of economic and legal policy of the state. The results of the study have a scientific novelty, as they fill the gap in the coverage of the role of the state in the process of digitalisation of the economy.